Penguatan Kompetensi Promosi Pariwisata Berbasis Inovasi Nilai di SMAN 20 Kabupaten Tangerang - Mansur, Suraya; restaty, Santa Margaretha Niken; Purba, Humiras Hardi (Jurnal PKM: Pengabdian Kepada Masyarakat, 2024)
One of the efforts to carry out promotions is by targeting attractive tourist objects, namely by creating content that attracts the attention of tourists. Interesting content must be captured or captured through posting photos and videos on social media or other communication media. These tourism promotion messages should be carried out by the whole community, especially the younger generation. Based on this, photography and videography skills are needed for the younger generation, as well as promoting them through social media. Photography is one of the media that can inform an object or event that occurs using pictures or visuals. Photography plays several important roles in describing an object and representing the actual object in an image medium. The purpose of community service activities at SMA Negeri 20 Tangerang Regency, Banten Province is to increase the competence of value innovation-based tourism promotion. The method used in this community service is direct observation, training and implementation and ends with an evaluation of the results of the activity. The results obtained from this activity are that students are able to understand the concept of value innovation in the field of photography and videography so that they can produce interesting and creative photo and video works for tourism development in Tangerang which are documented and published on the website.